2002
DOI: 10.1021/jo016352l
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(0)/Dihydroimidazol-2-ylidene Complex Catalyzed Coupling of Aryl Chlorides and Amines

Abstract: A general and simple nickel-catalyzed coupling of aryl chlorides and amines is reported. The scope and limitations of the coupling process using Ni(0), 1,3-bis(2,6-diisopropylphenyl)dihydroimidazol-2-ylidene, and NaO-t-Bu as base were investigated. Secondary cyclic and acyclic amines and anilines provided the arylamine coupling products in good to excellent yields. Compared to palladium-catalyzed aminations, this procedure offers an alternative route to N-substituted anilines starting from readily available ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
104
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(115 citation statements)
references
References 51 publications
11
104
0
Order By: Relevance
“…Physical and spectral data (mp, 1 H and 13 C NMR) of 3a were in agreement with the structure. 20 The scope and electronic effect of the present method were examined using a variety of substituted phenols and anilines. As shown in Table 1, m-and p-cresol, p-nitrophenol, and phydroxybenzaldehyde, and aniline, p-methoxyaniline, o-, m-, p-toluidine, p-nitroaniline were well tolerated in this reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Physical and spectral data (mp, 1 H and 13 C NMR) of 3a were in agreement with the structure. 20 The scope and electronic effect of the present method were examined using a variety of substituted phenols and anilines. As shown in Table 1, m-and p-cresol, p-nitrophenol, and phydroxybenzaldehyde, and aniline, p-methoxyaniline, o-, m-, p-toluidine, p-nitroaniline were well tolerated in this reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless the in situ generation of Ni(0) species starting from Ni(II) complexes are frequently used in catalysis usually in the presence of reducing agents such as organometallic species [60][61][62][63][64][65][66][67] or Zn dust [28,49]. As a matter of facts, in the present case, according to Fig.…”
Section: Influence Of Free Triphenylphosphine On the Catalytic Activitymentioning
confidence: 97%
“…Fort and coworkers have found that in situ generation of the Ni(0) and SIPr carbene efficiently catalyzes the coupling of aryl chlorides with various amines (Eq. 24) [58,59]. During the course of the study, it was discovered that Ni(0) could be generated from Ni(acac) 2 in the presence of NaH and t-BuOH.…”
Section: Amination Reactionsmentioning
confidence: 99%